Mesenchymal Stem Cell Therapy in Ischaemic Heart Failure: Hope or Hype? - Shiraz Hashmi; Mian Kamal Mustafa; Irfan Khan; Haseeb ur Rehman; Syed Shahabuddin; Shahid Sami (Journal of the Pakistan Medical Association, 2023)
Ischaemic heart diseases (IHDs) are the leading contributor to mortality worldwide and more than 60% occur in low-to-middle-income countries (LMICs) and 40% of these are specified as premature. Despite notable improvements in treatment options, premature deaths due to IHDs including ischaemic heart failure (IHF) continue to rise in the South Asian population due to prevalent conventional and inherent cardiovascular risk profiles. Stem cell (SCs) therapy has emerged as a potential frontier in regenerative therapy for acute and chronic illnesses. Among various available sources of SCs, the safety and efficacy of mesenchymal stem cells (MSCs) for non-functional cardiomyocytes have been established, but robust evidence necessitates to endorse these preliminary investigations. Little work has been conducted in resource constraints countries and needs immediate attention of all the stakeholders to explore non-conventional cost-effective and sustainable interventions for long term management of IHDs including IHF. Continued...